Nawrócenie jako temat poezji – droga Romana Brandstaettera do chrześcijaństwa - Wasilewska, Magdalena (Dydaktyka Polonistyczna, 2019)
The article discusses the subject of conversion as a subject of poetry on the example of the work of Roman Brandstaetter. It focused on the post-war creativity of the author, who in 1946 officially abandoned Judaism, received baptism and became a Catholic. Focused on two aspects of conversion. First of all, these were the circumstances of life: the need to leave the country, problems related to the Polish-Jewish identity, death of parents, parting with the first wife. Secondly, these were issues related to the biblical experience of God, because reading the Bible had a great significance for the poet since the time of Polish studies. Confirmations of the issue are confirmed by quotes from works that are testimonies of changes taking place in the author’s life, making up a rich picture of his spiritual transformation.